pengaruh pemberian pupuk organik cair kandang kelinci dan kompos limbah baglog pada pertumbuhan bibit Kakao (theobroma cacao l.) Di polibeg - Redho Anggara Nubriama; Erwin Pane; Sumihar Hutapea (Universitas Medan Area, 2019)
Cacao is one of the predominant plantation in Indonesia so that the production should be improved constantly. The purpose of this researce was to obtain data on the growth of cacao seedlings (Theobroma cacao L.) by applying rabbit cage liquid organic fertilizer and composting baglog waste with different doses. This research was carried out at the Medan Area faculty of agriculture experiment area located on the street PBSI No.1 Medan Estate. The research was conducted from July to November 2018. Using Factorial Randomized Group Desing (RGD) with two replications. The first factor tested was rabbit cage liquid organic fertilizer namely U0= without POC, U1= consentration 5% (50 ml POC/liter), U2= consentration 10% (100 ml POC/liter), U3= consentration 15% (150 ml POC/liter). The second factor is baglog waste compost which is L0= without compost baglog waste, L1= 20% baglog compost waste (600g) + 80% top soil (2.400g), L2= 40% baglog compost waste (1.200g) + 60% top soil (1.800g), L3= 60% baglog compost waste (1.800g) + 40% top soil (1.200g). The results showed that administration of baglog waste compost can increase growth ( plant height, number of leaves, stem diameter and canopy wet weight) of cocoa seedlings